ACE gene insertion/deletion polymorphism has a mild influence on the acute development of left ventricular dysfunction in patients with ST elevation myocardial infarction treated with primary PCI - Toman Ondrej; Tomcikova Daniela; Kubkova Lenka; Prymusova Krystyna; Manousek Jan; Poloczek Martin; Jarkovsky Jiri; Kala Petr; Goldbergova Monika; Parenica Jiri; Tesak Martin; Tomandl Josef; et al. (BMC Cardiovascular Disorders, 2010)
Abstract Background We evaluated the associations among angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism, ACE activity and post-myocardial infarction (MI) left ventricular dysfunction and acute heart failure (AHF) early after presentation with MI with ST-segment elevation (STEMI). Methods A total of 556 patients with STEMI treated by primary PCI (421 patients without AHF and 135 patients with AHF) were the study population. The activity of BNP, NT-ProBNP and ACE were measured at hospital admission and 24 h after MI onset. Left ventricular angiography was done before PCI; echocardiography was undertaken between the third and fifth day after MI. Results In comparison with the II genotypes group, the DD/ID group had a higher level of ACE activity upon hospital admission (p < 0.001). We found a significantly higher level of ACE activity in patients with moderate LV dysfunction (EF 40-54%) in comparison both with patients with preserved LV function (EF ≥55%) and with patients with severe LV dysfunction (p = 0.028). A non-significant trend towards a higher incidence of mild AHF (22.1% vs. 16.02%, p = 0,093), a significantly higher value of end-systolic volume (ESV/BSA) (30.0 ± 12.3 vs. 28.5 ± 13.0; p < 0.05) and lower EF (50.2 ± 11.1 vs. 52.7 ± 11.7; p < 0.05) in the DD/ID genotypes group was noted. Even after multiple adjustments according to multivariate models, the EF for the DD/ID group remained significantly lower (p = 0,033). The DD/ID genotypes were associated with a significantly higher risk of EF <45% (OR 2.04 [95% CI 1.28; 3.25]). Conclusions These results suggest that the I/D polymorphism of ACE is associated with the development of LV dysfunction in the acute phase after STEMI. We demonstrated for the first time an association of the low ACE activity with the severe LV dysfunction, although patients with moderate LV dysfunction had higher level ACE activity than patients with preserved LV function.